Estimation of subsurface structure based on microtremor observations at Padang, Indonesia. - Kiyono, Junji (Asean Engineering Journal)
In this study, we estimated a ground profile in Padang City, Indonesia, using microtremor observations. Indonesian is located on the boundaries of three major tectonic plates, namely the Indian-Australian, Pacific, and Eurasian plates. Consequently, subduction-related major earthquakes occur repeatedly, including even in the 21st century, such large inter-plate earthquakes as the 2004 Sumatra earthquake, the 2006 Nias Island earthquake, the 2007 Bengkulu earthquake, and the 2010 Mentawai earthquake. The 2009 Padang earthquake was also one of the most destructive earthquakes in recent times, although it was an intra-plate based earthquake. This earthquake was of magnitude Mw7.6, producing severe tremors and causing extensive damage to buildings and casualties. To prevent loss of human lives and dwellings from a devastating earthquake, we investigated the shaking characteristics of the ground in Padang. Spectral ratios for horizontal and vertical motion, H/V, from single station microtremor records were used to identify the predominant periods of the ground vibrations. Microtremor array observations were conducted to find the phase velocities of the Rayleigh wave. The ground profile was estimated by means of the dispersion curves obtained using the Spatial Autocorrelatio (SPAC) and Centerless Circular Array (CCA) methods. The Particle Swarm Optimization (PSO) technique was introduced to determine the dispersion curves. By compiling the soil profile model obtained at each site, a three layered generalized model was proposed. The velocity of the first layer was less than Vs=300 m/s, the second layer Vs=300-3000 m/s and the third layer more than Vs = 3,000 m/s. The subsurface structure models constructed provide useful information for 2-D and 3-D simulations of ground motion in Padang.